1982
DOI: 10.2355/isijinternational1966.22.838
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Study of Size Degradation Mechanism of Agglomerates during Reduction

Abstract: The mechanism of degradation of agglomerates during reduction is studied with pellets made from powdery ingredients of chemical reagent grade, and the changes in mineral phases due to certain oxides leading to degradation, are examined quantitatively. The results obtained are summarized as follows: (1) Microscopic observations suggest that cracking occurs in the skeletal hematite and the calcium ferrite phases. Analysis by line-broadening measurements of X-ray diffraction reveals no strain both in the bulky an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…Calcium ferrite is the major mineral constituent of the sinter structure and it imparts strength to the sintered mass. High content of calcium ferrites favors the tumbler strength of the sinter [15,16]. From the test results it was found that maximum 2.5 to 3.0 % (30 to 35kg/t of sinter) HMDS Slag can be used in the sinter making to achieve desired properties of the sinter as per the customer requirement .…”
Section: Figure 4 Process Chart For Integrated Slag Management Systemmentioning
confidence: 98%
“…Calcium ferrite is the major mineral constituent of the sinter structure and it imparts strength to the sintered mass. High content of calcium ferrites favors the tumbler strength of the sinter [15,16]. From the test results it was found that maximum 2.5 to 3.0 % (30 to 35kg/t of sinter) HMDS Slag can be used in the sinter making to achieve desired properties of the sinter as per the customer requirement .…”
Section: Figure 4 Process Chart For Integrated Slag Management Systemmentioning
confidence: 98%
“…El 铆ndice RDI tiene el valor m谩s bajo (es el mejor) para la mezcla mineral 3 (Tabla XI) y, esto, se puede asociar con el menor contenido en Al 2 O 3 de todas las mezclas (1,02 % Al 2 O 3 ) [28][29][30][31] y a la presencia de un contenido en MgO m谩s elevado en la mezcla, que resulta beneficioso para el RDI [32] .…”
Section: 铆Ndice Rdiunclassified
“…Calcium ferrite is the major mineral constituent of the sinter structure and it imparts strength to the sintered mass. High content of calcium ferrites favors the tumbler strength of the sinter [15,16].influence of HMDS Slag addition on sinter mean particle size and cum +10 mm percentage. In the present study sinter mean particle size was not influenced by the HMDS Slag addition.…”
Section: Experimental:-mentioning
confidence: 99%